Bimodal strategy for excellent audiological rehabilitation in a subject with a novel nonsense mutation of the SLC26A4 gene: A case report. (July 2020) - Malesci, Rita; Russo, Roberta; Monzillo, Carmela; Laria, Carla; Corvino, Virginia; Auletta, Gennaro; Iolascon, Achille; Franzè, Annamaria
Abstract: Sensorineural hearing loss is a heterogeneous disease caused by mutations in many genes. However, in the presence of enlarged vestibular aqueduct, it is frequently associated with mutations in the solute carrier family 26 member 4 ( SLC26A4 ), a gene causative of a syndromic form (Pendred) as well as a non-syndromic form of hearing loss (DFNB4). We describe a clinical case presenting bilateral sensorineural hearing loss and enlarged vestibular aqueduct in which a novel homozygous SLC26A4 mutation was identified. Despite a late diagnosis of hearing loss, a peculiar rehabilitation therapy strategy was identified that provided excellent results.